Komparasi Hasil Belajar Fiqih Qur-any antara Siswa Lulusan SD dengan MI Kelas VII C di MTs Al-Urwatul Wutsqo Jombang - Moch Sya'roni Hasan (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2022)
The problems that will be studied in this research are there differences in learning outcomes for Qur-any subjects (Tafsir Ahkam) between students who graduated from elementary school and students who graduated from MI in class VII male MTs Al-Urwatul Wutsqo Bulurejo Diwek Jombang? The population and sample in this study were male students of MTs grade VII at MTs Al-Urwatul Wutsqo Jombang. With a population of 36 students. The samples taken were 18 students from elementary schools and 18 students from Madrasah Ibtidaiyah. The analysis used is comparative analysis, with the "t" test analysis technique to state that there are differences in Islamic Religious Education learning outcomes between students from elementary school and students from MI in grade VII male MTs at Al-Urwatul Wutsqo Jombang. Based on the results obtained from the field and calculations using SPSS (t-test) it can be concluded that: 1). Learning Outcomes Between Elementary School Graduates and MI Students in Qur-any Subjects in class VII MTs Al-Urwatul Wutsqo Jombang are in the high category, based on research results the percentage is 58.33%. 2). Based on the results of statistical calculations with degrees of freedom (df) of 34 the 1% significance level is 1.30695 and the 5% significance level is 2.03224. While the tcount is 9.16 (tcount > ttable) from here it can be concluded that there is a difference in learning outcomes of Qur-any (Tafsir Ahkam) between elementary school graduates and MI students in Qur-any subjects in class VII MTs Al-Urwatul Wutsqo Jombang.